2014
DOI: 10.1111/cup.12363
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic onychomatricoma

Abstract: Figures 1 and 2 are depicted on the journal cover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The superficial layer is loose and wavy and contains mast cells, while the deeper layer is eosinophilic, hypocellular and densely fibrocollagenous. Rarely, pleomorphic and hyperchromatic, uninucleated and multinucleated giant cells are also present [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The superficial layer is loose and wavy and contains mast cells, while the deeper layer is eosinophilic, hypocellular and densely fibrocollagenous. Rarely, pleomorphic and hyperchromatic, uninucleated and multinucleated giant cells are also present [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, superficial acral fibromyxoma stains with CD99, perineurioma stains with EMA, and neurofibroma stains with S100. However, none of these tumors contain the epithelial-lined, spiky digitations of onychomatricoma that are best visualized on hematoxylin and eosin-stained sections [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stewart et al [35] reported an OM with prominent myxoid stroma associated with the fibrous component. Perrin et al [5] and Fernandez-Flores and Barja-Lopez [36] described a pleomorphic variant with wreath-like multinucleated cells along with zonal distribution of mast cells in the superficial stromal layer and membranous expression of CD34.…”
Section: Discussionmentioning
confidence: 99%